OPTIMALISASI SISTEM DIGITAL DALAM PENGELOLAAN DAN EFISIENSI ADMINISTRASI PENERIMAAN PESERTA DIDIK BARU DI SDQ UTRUJAH - Rahmah, Nailatur; Ali, Syaifi; Zahrah, Fatimatuz (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
This study aims to explain the management and efficiency of the administration of New Student Admissions (PPDB) using a digital system at SDQ Utrujah. The importance of optimizing the digital system in improving the management and efficiency of the quality of administrative services in basic education is the background of this study. A descriptive qualitative approach is used as a research method. Data collection techniques through semi-structured interviews, observations, and documentation using source triangulation. The results obtained show that the digital system implemented at SDQ simplifies and accelerates administrative activities in New Student Admissions, thereby reducing physical documents and data transparency. This digitalization system also makes it easier for parents of students to access registration forms and technical guides for activities. The obstacles faced are given individual direction and guidance to be more appropriate. It can be concluded that the digital system in the administration of New Student Admissions at SDQ Utrujah has a very positive impact on the management and efficiency of administration in educational services at the school.